Puerto Rico's minimum wage: Revisiting a price floor with bite - Robert Tucker Omberg (IZA Journal of Labor Policy, 2021)
Revisiting research from the 1990s from Castillo-Freeman and Krueger, I use the synthetic control method of Abadie et al. to estimate the impact of the most recent increase in the federal minimum wage on employment in Puerto Rico. I estimate that the employment/population ratio of various groups in Puerto Rico was significantly lower than that of a data-constructed synthetic Puerto Rico which did not raise its minimum wage. Placebo tests on other donor units, time periods, and population groups suggest that a significant portion of this gap is a result of the minimum wage. Groups with greater exposure to the minimum wage, such as teens and restaurant workers, experienced proportionally greater declines in employment. My results suggest an own-wage elasticity of employment in Puerto Rico of -0.68, higher than estimates from the mainland, which suggests that the employment response to minimum wages may be more dramatic at higher relative minimum wages.
Keywords: J01; J08; J40; 330; Minimum Wage; Puerto Rico; Synthetic Controls